Nanoparticle Self‐Assembly: Two‐Step Assembly of Thermoresponsive Gold Nanorods Coated with a Single Kind of Ligand (Small 14/2018). Issue 14 (6th April 2018) - Iida, Ryo; Mitomo, Hideyuki; Niikura, Kenichi; Matsuo, Yasutaka; Ijiro, Kuniharu
Abstract : In article number1704230, Hideyuki Mitomo, Kuniharu Ijiro, and co‐workers introduce a thermoresponsive two‐step assembly of rod‐shaped gold nanoparticles (GNRs) by a simple surface modification with a single kind of ligand. As dehydration temperature of the surface ligand varies depending on the degree of curvature, GNRs form side‐by‐side assemblies first, and then form assembled‐assemblies on heating, providing hierarchical structures.